Marketing Management of Islamic Boarding Schools in Enhancing Public Trust at Darul Hikmah Islamic Boarding School, Tulungagung (Lembaga Pengembangan Kinerja Dosen, 2025)
The management of educational institutions has a strategic role in determining the direction of growth and sustainability of the institution. The success of this management is highly dependent on the administrator's ability to analyze the external environment, understand the position of competitors, optimize internal potential, and formulate superior strategies that are able to maintain competitiveness without ignoring the fundamental values ​​of education. In this context, the application of marketing management becomes an important need. This study aims to analyze marketing management in increasing public trust in the Darul Hikmah Islamic Boarding School in Tulungagung. This study uses a qualitative phenomenological approach with data collection techniques through interviews, observations, and documentation. Data analysis is carried out through data condensation, data presentation, and drawing conclusion/verification. The results of the study indicate that the marketing strategy of the Darul Hikmah Islamic Boarding School in Tulungagung in building public trust is implemented through four main elements: (1) Product – offering quality educational services with character strengthening, implementing the curriculum of the Ministry of National Education, Ministry of Religious Affairs, local content, and superior extracurricular programs; (2) Price – affordable registration and administration fees and adjusted to the economic conditions of the community; (3) Place – the location of the Islamic boarding school is strategic, easy to reach, and has a conducive learning environment; and (4) Promotion – conducted through visits to elementary schools, installation of promotional media (billboards, banners, brochures), publication of extracurricular achievements, and utilization of social media such as Facebook, Instagram, YouTube, and the Islamic boarding school's official website.